The effect of core electrons in e(+)-Na scattering - Ray, H.; Chaudhuri, P.; Ghosh, A. S. (Iop Publishing Ltd, 1998)
The scattering of positrons off sodium targets has been investigated using the coupled static model. The sodium atom is represented by the one-active-electron model in which all the electrons of the target have been considered explicitly and the loosely bound valence electron is only involved in transitions. The scattering parameters are presented at low and medium energies. Appreciable differences are noticed between the present results and those obtained by the one-electron model with and without the core potential.